DESAIN PEMBELAJARAN KHOT BERBASIS STUDENT DIRECTED LEARNING UNTUK SISWA SEKOLAH MENENGAH - Auliya, Hazmi; Mukmin; Nurul Hidayah; Nanda Afwannisa; Muhammad Fariz Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to write in Arabic (Maharah Kitabah) often poses a challenge for junior high school students due to the lack of engaging teaching materials and teacher-centered learning approaches. This study aims to develop Student Worksheets (LKPD) based on Ana Muhtarif Al-Khat using the Student Directed Learning (SDL) approach to enhance Arabic writing skills. The research method employs Research and Development (R&D) with a simplified Borg and Gall model consisting of six stages. The results show a significant increase in students' average scores from 62 (pre-test) to 87 (post-test), with material and media validation scores reaching 100 and 84, respectively. The implication of this study is that technology-based LKPD can serve as an innovative solution to improve students' independence and writing skills, while also opening opportunities for the development of similar teaching materials for other Arabic language skills.